On Some Lacunary Almost Convergent Double Sequence Spaces and Banach Limits - Metin Başarır; Şükran Konca (Abstract and Applied Analysis)
The object of this paper is to introduce some new sequence spaces related with the concept of lacunary strong almost convergence for double sequences and also to characterize these spaces through sublinear functionals that both dominate and generate Banach limits and to establish some inclusion relations.